Opérations traductives dans les processus créatif et de conception en design - Sophie Fétro (Appareil)
Micro-phenomena of translation are present in the design work that are part of the designer’s creative work, going against the idea of a unilateral, linear and time-concentrated design. In reality, translation phenomena are present in a multitude of moments, through different media, during production, through collaborative work and by third parties. Computer technology has added possible spaces for interpretation, notably due to computer coding and format changes, but also automated procedures that can also reduce the designer’s intervention, choice and interpretation moments. The article thus proposes to distinguish three types of translation situations and to question what the translation methods put in place, invented or deduced from the techniques used, can allow on the creative level, leading to the belief that it is the set of translation operations that constitutes the creative work of designers. It is by distinguishing three types of translation that this article will consider the notion and act of translation in the field of conception and design: 1/ figurative and three-dimensional translations; 2/ matrix and graphical translations; 3/ software and hardware translations. The translation process in the form of matrices and graphs that Anthony Fröshaug, a teacher at the HfG in Ulm, is setting up will be central and will make it possible to articulate more classical modes of translation in design (drawings and models) with computer translation processes